AB1233 Does time matter? a systematic review to assess the relationship between delay in diagnosis and costs in dmard-naÏve ra patients. (12th June 2018) - Sahbudin, I.; Singh, R.; Trickey, J.; Tracy, A.; Raza, K.; Filer, A.; Boonen, A.
Abstract : Background: Early diagnosis is crucial to enable timely DMARDs initiation in RA patients. Although, early treatment improves clinical outcomes, it is unclear whether this has a similar impact on health economic outcomes. Early DMARDs intervention may avert the requirement of expensive biological therapy as second-line treatment, which leads to improved overall cost-effectiveness. As a first step to address this issue, we performed a systematic literature review to appraise existing evidence relating to delay in diagnosis and cost-of-illness in DMARD-naïve newly-diagnosed RA patients. Objectives: To identify whether disease duration before initiation of first DMARD therapy is a determinant of subsequent direct and indirect costs in DMARD-naïve RA patients. Methods: We systematically searched Pubmed, EMBASE, CINAHL and Medline databases for published literature relating to rheumatoid arthritis, and direct and/or indirect costs. We included studies with DMARD-naïve patients who fulfilled the 1987 ACR or 2010 ACR/EULAR classification criteria for RA. We excluded: 1 studies on non-rheumatoid arthritis patients; 2 conference abstracts, systematic reviews or review articles; 3 studies with no documented symptom duration prior to diagnosis; 4 studies which did not report direct and/or direct costs and/or health utilisation. All studies were required to report their methods and sources of respective cost measurements. We extracted the following data from each study; 1 study design; 2 potential determinants of RA cost; 3 health economic outcomes and 4 source of unit cost for the health-resources. Results: A total of 173 records were identified in the systematic search, five of which included in the analysis. Two were cost-of-illness studies within the context of observational studies and the remaining were cost-of-illness studies alongside clinical trials. The health outcomes reported were heterogeneous: 1) Direct medical costs were reported in three studies; 2) Indirect non-medical costs were reported in one study and 3) Health-care utilisation was reported in one study. Only one study reported indirect costs from the societal perspective e.g. work disability. The definition of symptom duration was not specified in any studies. Three studies reported disease duration of one year or less and two studies reported symptom duration of six months and <two years. The timing and duration of the reported health economic outcomes varied widely (figure 1). The direct medical costs for three papers were adjusted for purchasing power parities and consumer price index for 2017 US Dollars. Conclusions: Data on the relationship between symptom duration and costs in DMARD-naïve RA patients is limited. Comparability between studies is hampered due to heterogeneity of the definition for symptom/disease duration and the health economic outcomes reported. An inception cohort of suspected/early RA should include data in resource utilisation and costs studies to identify the relationship between symptom duration and health economic outcomes. Disclosure of Interest: None declared